Factors associated with stigma related to HIV pre-exposure prophylaxis (PrEP) use among men who have sex with men (MSM). (4th February 2022) - Bhatta, Dharma N; Hecht, Jennifer; Facente, Shelley N
Abstract : Background: Pre-exposure prophylaxis (PrEP) is a noteworthy scientific development that increases the opportunities for men who have sex with men (MSM) to prevent HIV infection, but stigma is a major barrier to its uptake. This study aims to determine the associations between PrEP-related stigma and individual characteristics among MSM. Methods: Self-reported cross-sectional data were collected from routine-collected electronic healthcare record data from 4084 MSM receiving PrEP in San Francisco, California, between July 2018 and June 2020. Multivariable logistic regression was performed to determine the associations between individual characteristics and PrEP-related stigma, adjusting for age, race, gender identity, injection history, housing status and mental health status. Results: PrEP-related stigma was experienced by 9.0% of the participants in our study. PrEP-related stigma was significantly associated with being transgender or gender non-conforming (adjusted OR (AOR): 1.81, 95% CI 1.21 to 2.72), having a history of injection drug use (AOR: 2.02, 95% CI 1.18 to 3.46), being unstably housed (AOR: 1.58, 95% CI 1.11 to 2.26) and having mental health concerns (AOR: 1.99, 95% CI 1.35 to 2.92), after controlling for age, race, gender, injection history, housing status and mental health status. Conclusion: Participants who reported being transgender or gender non-conforming, having a history of injection drug use, or having mental health concerns were more likely to report experiencing PrEP-related stigma. It is crucial to develop culturally appropriate interventions to reduce PrEP-related stigma among populations who are at high risk of HIV infection and may benefit strongly from improved PrEP uptake.